Effect of Trehalose and Trehalose Transport on the Tolerance of Clostridium perfringens to Environmental Stress in a Wild Type Strain and Its Fluoroquinolone-Resistant Mutant - Miseon Park; Wilfrid J. Mitchell; Fatemeh Rafii (International Journal of Microbiology)
Trehalose has been shown to protect bacterial cells from environmental stress. Its uptake and osmoprotective effect in Clostridium perfringens were investigated by comparing wild type C. perfringens ATCC 13124 with a fluoroquinolone- (gatifloxacin-) resistant mutant. In a chemically defined medium, trehalose and sucrose supported the growth of the wild type but not that of the mutant. Microarray data and qRT-PCR showed that putative genes for the phosphorylation and transport of sucrose and trehalose (via phosphoenolpyruvate-dependent phosphotransferase systems, PTS) and some regulatory genes were downregulated in the mutant. The wild type had greater tolerance than the mutant to salts and low pH; trehalose and sucrose further enhanced the osmotolerance of the wild type to NaCl. Expression of the trehalose-specific PTS was lower in the fluoroquinolone-resistant mutant. Protection of C. perfringens from environmental stress could therefore be correlated with the ability to take up trehalose.